The prevalence and impact of unprofessional behaviour among hospital workers: a survey in seven Australian hospitals - Westbrook, Johanna; Sunderland, Neroli; Li, Ling; Koyama, Alain; McMullan, Ryan; Urwin, Rachel; Churruca, Kate; Baysari, Melissa T; Jones, Catherine; Loh, Erwin; McInnes, Elizabeth C; Middleton, Sandy; et al. (Medical journal of Australia, 2021)
Objective To identify individual and organisational factors associated with the prevalence, type and impact of unprofessional behaviours among hospital employees. Design, setting, participants Staff in seven metropolitan tertiary hospitals operated by one health care provider in three states were surveyed (Dec 2017 – Nov 2018) about their experience of unprofessional behaviours — 21 classified as incivility or bullying and five as extreme unprofessional behaviour (eg, sexual or physical assault) — and their perceived impact on personal wellbeing, teamwork and care quality, as well as about their speaking‐up skills. Main outcome measures Frequency of experiencing 26 unprofessional behaviours during the preceding 12 months; factors associated with experiencing unprofessional behaviour and its impact, including self‐reported speaking‐up skills. Results Valid surveys (more than 60% of questions answered) were submitted by 5178 of an estimated 15 213 staff members (response rate, 34.0%). 4846 respondents (93.6%; 95% CI, 92.9–94.2%) reported experiencing at least one unprofessional behaviour during the preceding year, including 2009 (38.8%; 95% CI, 37.5–40.1%) who reported weekly or more frequent incivility or bullying; 753 (14.5%; 95% CI, 13.6–15.5%) reported extreme unprofessional behaviour. Nurses and non‐clinical staff members aged 25–34 years reported incivility/bullying and extreme behaviour more often than other staff and age groups respectively. Staff with self‐reported speaking‐up skills experienced less incivility/bullying (odds ratio [OR], 0.53; 95% CI, 0.46–0.61) and extreme behaviour (OR, 0.80; 95% CI, 0.67–0.97), and also less frequently an impact on their personal wellbeing (OR, 0.44; 95% CI, 0.38–0.51). Conclusions Unprofessional behaviour is common among hospital workers. Tolerance for low level poor behaviour may be an enabler for more serious misbehaviour that endangers staff wellbeing and patient safety. Training staff about speaking up is required, together with organisational processes for effectively eliminating unprofessional behaviour.